(untitled) (American Journal of Islam and Society, 2014)
Setrag Manoukian’s City of Knowledge in Twentieth Century Iran: Shiraz, History, and Poetry combines the application of Michel Foucault’s conceptualization of the relationship between “knowledge” and “power” with a “historical and ethnographic investigation” into the sociocultural and political life of twentieth-century Shiraz in order to portray a history of Iran and Iranians that differs from the usual accounts focusing on Tehran. The book is intended for both Iranian studies scholars and the general public interested in the history of Iran. Avoiding an exclusivist approach that Book Reviews 107 offers either “a national perspective from the capital Tehran” or “a purely local view from a self-contained city,” the book provides, in the author’s words, “the viewpoint of Shiraz as a ‘province’ to highlight how local, national and global dimensions are mutually constituted.” It discusses the “question of knowledge” from the viewpoint of Shiraz because most of the research on contemporary Iran concentrates on the capital as representative of the whole country. In his view, “the after-effect of this concentration on Tehran is an analytical posture that posits either the state and/or the nation as the starting points of the analysis, obliterating the multiplicity of convergences and divergences from which both these constituencies emerge” (p. 3) ...